STRATEGI PENGUSAHA WARUNG KOPI FIFA 99, DALAM MEMPERTAHANKAN KONSUMEN PERSPEKTIF ETIKA BISNIS ISLAM DI PERUMAHAN MENGANTI SATELIT INDAH (Studi Kasus Warung Kopi FiFa 99, di Perumahan MSI) - Graha Bima Tara, Mukhammad Afif; Sutono, Sutono (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2023)
Keywords: Strategy, Coffee Shop, Islamic Business Ethics The research in this thesis is motivated by the increasing number of unemployed in Gresik due to the difficulty of finding work in the formal sector. Seeing the habits of the people, especially men in Gresik Regency, who like to consume coffee drinks, this situation has become an opportunity to set up a coffee shop business. In Gresik you can find many coffee shop businesses, but many of these coffee shops are still classified as micro businesses that have been established for years but have not been able to develop. In this case, the researcher tested what factors influence the success of the coffee shop business in Menganti Satellite Indah Housing, so that the results of this research can be used as input and used as motivation so that entrepreneurs want to improve and develop their business in order to achieve the target, namely success in entrepreneurship. So that later it can be used as a choice for people in entrepreneurship to create jobs and reduce unemployment. This research focuses on what factors influence the success of the Fifa 99 coffee shop business in Menganti Satellite Indah Gresik Housing, whether there is an influence between factor 1 (capital, planning and location) on the success of the Fifa 99 coffee shop business in Menganti Satellite Housing. Beautiful Gresik. This research uses a qualitative approach with an ex post facto type of research. The data collection technique in this research uses a questionnaire method. The type of data used in this research is primary data obtained from the results of a questionnaire that was filled out by the owner of a coffee shop business in the Menganti Satelit Indah Menganti Housing Complex, Gresik, which was used as the sample in this research. The data analysis method uses validity and reliability tests, factor analysis then assumption tests and simple linear regression. Based on the results of the analysis, it can be concluded that of the seven variables, namely entrepreneurial characteristics, capital, opportunities, planning, location, marketing and experience studied, there is one factor that influences the success of the coffee shop business in Menganti Satellite Indah Gresik Housing. namely factor 1 capital, planning and strategic location.